New insights of potential biomarkers in diabetic retinopathy: integrated multi-omic analyses - Wang, Xurui; Liu, Weina; Zheng, Xiujin; Yang, Ming Ming (Frontiers in Endocrinology, 2025)
Diabetes mellitus prevalence is rising worldwide, with a predicted 20% increase between 2021 and 2030, bringing an increased burden of complications such as diabetic retinopathy (DR). DR is a common and serious ocular complication of diabetes, and one of the most common irreversible blinding ophthalmic diseases. Its pathogenesis is intricate and complex, involving hypoxia, oxidative stress, inflammation, abnormalities in the polyol metabolic pathway, and others. Clinical detection of DR is impeded by atypical early symptoms, imperfect imaging screening tools, ocular comorbidities (e.g., cataract), and shortages of human resources. Therefore, more in-depth studies are needed to improve DR diagnosis and identify higher-risk patients. “Omics” encompasses genomics, transcriptomics, proteomics, and metabolomics. Omics technologies are increasingly used in research seeking to identify biomarkers or early preclinical signs of disease, or to better understand complex pathological processes determining disease prognosis. And DR is no exception, as an area in need of improved understanding and prognosis. To date, research has yielded significant results advancing DR diagnosis and treatment, informing prevention strategies and reducing global disease impact. This article reviewed recent findings of omics in DR diagnosis and treatment, improving our understanding of DR pathology and enabling personalized treatments.